The Scientometrics of Social Entrepreneurship and Its Establishment as an Academic Field - Sassmannshausen, Sean Patrick; Volkmann, Christine (Journal of Small Business Management, 2018)
This paper provides an overview of the state of art of research on social entrepreneurship and the establishment of this topic in the academic world. It uses scientometric methods in measuring the maturity of social entrepreneurship research. The empirical part reveals the exponentially growing number of papers, the institutionalization of social entrepreneurship in seven dimensions, the emergence of thematic clusters, and methodological issues. The paper makes concrete suggestions on how to overcome methodological challenges. Furthermore, we provide a ranking of the 22 most cited academic contributions in social entrepreneurship. Surprisingly, almost half of the most cited papers have not been published in journals but in books, raising doubts about the current (over-)rating of journal publications.
Keywords: Entrepreneuriat social; Réservé UdeM; Scientométrie; Université